The amazing book of mammal records : the largest, the smallest, the fastest, and many more! - Woods, Samuel G.; Cline, Jeff (Woodbridge, Conn. : Blackbirch Press, 2000)
Introduces, in question and answer format, such record- breaking mammals as the cheetah, blue whale, koala, giraffe, and water buffalo.
Includes bibliographical references (p. 32).
IG 880
Accelerated Reader AR
Keywords: Mammals -- Miscellanea -- Juvenile literature; Mammals -- Miscellanea; Questions and answers